Electrocardiographic Changes after Spontaneous Intracerebral Hemorrhage - Bhargava, Pranshu; Singh, Rahul (Indian Journal of Neurosurgery, 2019)
Introduction Electrocardiographic (ECG) changes after ischemic stroke are well documented. However, ECG changes after spontaneous intracerebral hemorrhage (SICH) have been infrequently studied. In many cases, changes occur due to neurogenic causes and may be misinterpreted as primary cardiac events.Aims This study was undertaken to study ECG changes after SICH.Materials and Method This study included all SICH patients admitted over 1 year. Patients with intraventricular and subarachnoid hemorrhage without cerebral bleed were excluded, and those with a doubtful history of head injury were also excluded. Management was guided as per standard protocol. All patients were monitored in neurosurgical intensive care unit (ICU). ECG changes were noted and analyzed.Results Total 47 SICH patients were admitted over 1 year; 0.66% patients were found to have one or more ECG abnormalities at time of admission. A prolonged QTc interval was the most common finding (39%), followed by sinus tachycardia or bradycardia and ST-segment changes. All patients with brainstem or intraventricular bleed had changes in ECG, whereas 62% had basal ganglia (BG) bleed, 43% thalamic bleed, and 57% had cortical bleeds had ECG changes, and 0.13% of patients had concomitant echocardiographic (ECHO) changes also. The most common change in BG lesion was T inversion as well as QTc prolongation in thalamic lesions. An equal percentage of males and females had ECG changes; however, 80% of all patients were males. All patients younger than 40 years had changes on ECG, and 75% of patients in the age group of 61 to 70 were found to have changes on ECG. In one patient with intraventricular hemorrhagic, global hypokinesia was reversed after insertion of ventricular drain and normalization of intracranial pressure (ICP). Although the management of the cardiac events may remain the same, in cases in which the primary cause is neurogenic, treating this cause or lowering ICP may help in reverting ECG changes.Conclusion ECG changes occurring after SICH need to be cautiously interpreted, as the primary cause may be neurogenic and subsequent treatment would require lowering of ICP either surgically or medically.
Keywords: electrocardiographic; intracranial; hemorrhage